Transformations in a Ti-24Al- 15Nb alloy: Part II. a composition invariant βo → O transformation - Muraleedharan K.; Nandy T.K.; Banerjee D.; Lele S. (My University, 2025)
This article explores the nature of a composition invariant phase transformation from β o(B2, Ti2AlNb) to an orthorhombic O phase (Cmcm) on aging a β quenched Ti-24Al-15Nb alloy. The transformation product is shown to contain a variety of defect structures whose origins are analyzed and explained. The orthorhombic phase is shown in exist in two forms: (1) in which the Nb atoms occupy a specific sublattice and (2) in which the Nb and Ti atoms randomly occupy the same sublattice. The subsequent decomposition of the metastable O product into the equilibrium phases is also described. © 1992 The Minerals, Metals and Materials Society, and ASM International.